2022
DOI: 10.1186/s12883-022-02854-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical factors associated with cerebral autoregulation in ischemic stroke related to small artery occlusion

Abstract: Background Existing data suggest that cerebral autoregulation (CA) varies among different subtypes of ischaemic stroke. CA is globally impaired in patients with small artery occlusion (SAO). However, the factors influencing CA impairment in patients remains to be elucidated. Methods Stroke patients with SAO who underwent brain magnetic resonance imaging (MRI) were prospectively studied. Within 7 days after stroke onset, CA was recorded from the mid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Guo et al 102 extended the findings from these studies by following up the patients after initial cross‐sectional analysis and demonstrated that the observation of impaired cerebral autoregulation in the groups with cSVD was diffuse and persisted for 6 months after the initial lacunar infarction. Contrary to most studies included, both Wu et al 106 and Xiong et al 105 reported no association between cerebral autoregulation and any radiological markers of cSVD. However, both studies used approaches to determining cerebral autoregulation that differed from those previously discussed.…”
Section: Resultsmentioning
confidence: 78%
See 4 more Smart Citations
“…Guo et al 102 extended the findings from these studies by following up the patients after initial cross‐sectional analysis and demonstrated that the observation of impaired cerebral autoregulation in the groups with cSVD was diffuse and persisted for 6 months after the initial lacunar infarction. Contrary to most studies included, both Wu et al 106 and Xiong et al 105 reported no association between cerebral autoregulation and any radiological markers of cSVD. However, both studies used approaches to determining cerebral autoregulation that differed from those previously discussed.…”
Section: Resultsmentioning
confidence: 78%
“…All 102 , 103 , 104 , 107 , 108 , 109 , 110 , 111 , 112 , 114 , 115 but 3 105 , 106 , 113 studies demonstrated a significant association between cerebral autoregulation impairments and greater cSVD burden. Six studies were case–control studies 102 , 103 , 105 , 107 , 108 , 113 and 8 studies were prospective or retrospective cohort studies.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations